Public communication and behavior. - Comstock, George (George A.) (Academic Press, 1986)
Public Communication and Behavior, Volume 1 covers the study of communicatory behavior that has a public or social character. The book discusses the evaluation of the models used to evaluate television series; the synthesis of 1043 effects of television on social behavior; and tv news, priming, and public evaluations of the president. The text also describes the myth of massive media impact; and the new technique for assessing the impact of mass media violence on real-world aggressive behavior. Social psychologists will find the book invaluable.